2020
DOI: 10.1186/s13031-020-00273-1
|View full text |Cite
|
Sign up to set email alerts
|

Health in conflict and post-conflict settings: reproductive, maternal and child health in Colombia

Abstract: Background: In conflict-afflicted areas, pregnant women and newborns often have higher rates of adverse health outcomes. Objective: To describe maternal and child health indicators and interventions between 1998 and 2016 comparing high and low conflict areas in Colombia. Methods: Mixed study of convergent triangulation. In the quantitative component, 16 indicators were calculated using official, secondary data sources. The victimization rate resulting from armed conflict was calculated by municipality and grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…Research from Afghanistan showed that coverage of skilled birth attendants and institutional facility deliveries continued to increase linearly between 2003 (approximately 20%) and 2015 (approximately 50%), when the country experienced substantial national conflict, explained by early investment in maternal health programmes and a resilient health system [ 37 ]. A similar pattern was recently documented in Colombia [ 43 ]. The absence of a significant relationship between conflict and neonatal mortality indicates that mechanisms underlying the association between conflict and maternal and child health may be complex and may vary between outcome measures.…”
Section: Discussionsupporting
confidence: 88%
“…Research from Afghanistan showed that coverage of skilled birth attendants and institutional facility deliveries continued to increase linearly between 2003 (approximately 20%) and 2015 (approximately 50%), when the country experienced substantial national conflict, explained by early investment in maternal health programmes and a resilient health system [ 37 ]. A similar pattern was recently documented in Colombia [ 43 ]. The absence of a significant relationship between conflict and neonatal mortality indicates that mechanisms underlying the association between conflict and maternal and child health may be complex and may vary between outcome measures.…”
Section: Discussionsupporting
confidence: 88%
“…We posit that while conflict was not a frequently cited barrier, it may largely explain women’s poor uptake of ANC. For example, in some FCAS, healthcare facilities are attacked, practitioners may be kidnapped, killed, or forced to flee to urban areas to ensure safety, and clinics often lack necessary resources [ 83 ]. These events may explain why women experience poor quality of ANC and cannot find care facilities in rural areas [ 6 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women reported experiencing long wait times and receiving care from providers who were unfriendly and “inept” [ 30 ]. Conflict directly affects resource allocation and contributes to a lack of providers, equipment, and medical resources, which may explain the poor quality of care [ 83 ]. Pregnant women in FCAS are a vulnerable population who are often unaware of the benefits of ANC [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we present the findings of a social innovation case study developed and implemented in a rural post-conflict region in Colombia with the purpose of comprehensively addressing the health needs of the local population and enhancing health service access [ 24 ].. The social innovation - ‘ Model of Integral Health Care for Rural Areas, in the rural town of Sumapaz (Bogotá, Colombia)’ - has been implemented as a primary care initiative by the Subred Sur (the main public health institution of the district) for the past 20 years.…”
Section: Introductionmentioning
confidence: 99%